Ancylomenes australis sp. nov. (Crustacea: Decapoda: Pontoniinae) from South Africa - Bruce, A. J. (Zootaxa, 2013)
The holotype specimen of Ancylomenes australis, new species, (Crustacea: Decapoda: Pontoniinae) from Sodwana Bay, South Africa, is described and illustrated. It is the only species of the genus reported from south east Africa. It is an associate of cerianthid anemones and has a species specific colour pattern. Closely similar to A. venustus (Bruce, 1990) it is readily distinguished from it and all other species of the genus by its characteristic rostrum and blunt inferior orbital angle.